Detrital zircon geochronology and heavy mineral analysis as complementary provenance tools in the presence of extensive weathering, reworking and recycling: the Neogene of the southern North Sea Basin. (30th September 2021) - Verhaegen, Jasper; von Eynatten, Hilmar; Dunkl, István; Weltje, Gert Jan
Abstract: Heavy mineral analysis is a long-standing and valuable tool for sedimentary provenance analysis. Many studies have indicated that heavy mineral data can also be significantly affected by hydraulic sorting, weathering and reworking or recycling, leading to incomplete or erroneous provenance interpretations if they are used in isolation. By combining zircon U–Pb geochronology with heavy mineral data for the southern North Sea Basin, this study shows that the classic model of sediment mixing between a northern and a southern source throughout the Neogene is more complex. In contrast to the strongly variable heavy mineral composition, the zircon U–Pb age spectra are mostly constant for the studied samples. This provides a strong indication that most zircons had an initial similar northern source, yet the sediment has undergone intense chemical weathering on top of the Brabant Massif and Ardennes in the south. This weathered sediment was later recycled into the southern North Sea Basin through local rivers and the Meuse, leading to a weathered southern heavy mineral signature and a fresh northern heavy mineral signature, yet exhibiting a constant zircon U–Pb age signature. Thus, this study highlights the necessity of combining multiple provenance proxies to correctly account for weathering, reworking and recycling.